Association between LPS data and accelerometer-based metrics: breaking antennas dependency for external load monitoring in women`s handball - García-Sánchez, C.; Nieto-Acevedo, R.; Martínez-Rubio, C.; Marquina, M.; Navarro, R. M.; de la Rubia, A. (International Journal of Performance Analysis in Sport, 2026)
Scientific evidence on the relationship between speed-based metrics from local positioning systems (LPS) and accelerometer-based metrics from inertial measurement units (IMUs) in women`s handball is limited. This study aimed to (1) examine associations between LPS and IMU metrics by playing position; (2) determine the predictive capacity of LPS metrics from IMU data; and (3) provide reference values in novel LPS and IMU metrics. Very strong correlations were found between total distance covered (TDC) and PlayerLoad (PL) across all positions (p < 0.001; r = 0.952-0.992), suggesting both can quantify external load volume. High metabolic load distance (HMLD) showed strong associations with accumulated PL above 2 G (+2 G-PL) (r = 0.719-0.955), accumulated PL above 4 G (+4 G-PL) (r = 0.603-0.905), and dynamic stress load (DSL) (r = 0.510-0.832), indicating their relevance as intensity metrics. Linear regression models revealed that TDC can be predicted by PL for all positions (R2 = 0.906-0.984; p < 0.001), while HMLD can be predicted by +2 G-PL for pivots and wings (R2 = 0.761 and 0.913, respectively), and by +4 G-PL and DSL for wings (R2 = 0.819 and 0.693, respectively). These findings support the use of accelerometer-based metrics to monitor both volume and intensity metrics, offering practical alternatives when LPS antennas are unavailable.